Rubberized reinforced concrete columns under axial and cyclic loading (Fracture and Structural Integrity, 2024)
The experimental study presented in this research was conducted to understand the performance of rubberized concrete columns under axial loads and numerically analyze the conduct of rubberized reinforced concrete (RRC) columns under cyclic loads. Twelve large-scale columns with square and circular cross sections were utilized to carry out experimental testing. Under axial loading, fine aggregate was replaced in percentages of 0%, 10%, and 15% with crumb rubber (CR). Square RRC columns were examined by a finite element program (ABAQUS) under cyclic loading. The experimental results indicated that the columns with crumb rubber had a lower load capacity than those without crumb rubber when exposed to axial loads. The numerical results were in good alignment with the experimental results, indicating that the simulated model may simulate the behavior of rubberized concrete columns under both axial and cyclic loads. According to the numerical analyses, the lateral displacement was significantly improved for rubberized reinforced concrete columns with 10% and 15% replacement of fine aggregates compared to columns without CR. Adding 10% and 15% of crump rubber to the fine aggregate in reinforced concrete columns increased the displacement ductility. The equivalent viscous damping ratio was enhanced by 33.67% when increasing crumb rubber (CR) from 0% to 10%, and when crumb rubber (CR) replacement became 15%, the damping ratio increased to 44.02%.The rubberized reinforced concrete columns showed a more ductile reaction than the traditional reinforced concrete columns, as evidenced by their softer post-peak response.
Keywords: Crumb Rubber; Axial loading; Cyclic loading